ECONOMIC IMPACT ANALYSIS IN GOVERNMENT REGULATION NUMBER 26 OF 2023 CONCERNING MANAGEMENT OF SEDIMENTATION PRODUCTS IN THE SEA - Dela Kholidatul Ummah; Nurul Huda (Jurnal Ekonomi, 2023)
Based on Government Regulation no. 26 of 2023 concerning management of sedimentation results in the sea. This research aims to find out the economic and environmental impacts that occurred as a result of the passing of Government Regulation no. 26 of 2023 concerning management of sedimentation results in the sea. This research uses a qualitative approach using the desk study method, namely a way of collecting data and information through data examination and analysis, using secondary data in the form of internal/external documents, government regulations, statistical data, literature studies, maps and the internet, and the data analysis technique used in this research uses Milles and Hubberman's theory, namely the steps of data reduction, data presentation and finally drawing conclusions. The results of the research show that the economic and environmental impact due to the management of marine sedimentation as ratified by Government Regulation Number 26 of 2023 on coastal communities has quite a significant impact, as felt by the coastal communities of the Riau Islands, namely that they have to experience reduced fish catches, this is of course due to due to fish habitat (undersea ecosystem) which has been damaged due to sea sand dredging, apart from that, fishermen's operational costs for going to sea are increasingly expensive because they have to spend more money to buy diesel/ship fuel, because the fishing areas are increasingly far from This is the impact of sand dredging and marine sedimentation management that lacks supervision from the government, as well as minimal punishment for investors/business actors who violate management regulations.